Pemberdayaan Perempuan dalam Penyelenggaraan Otonomi Daerah - Ria Fitri (Universitas Syiah Kuala, 2010)
ABSTRACT: Non equality and non equity of gender still there are in Aceh society. Autonomous of area area enableness of woman and protection of child give wide of room at Government of Acheh, governmental of sub-province / town isn't it him, start from the energy and policy of him. This matter can know accomodated by issues him of gender in made qanun-qanun pursuant to comand of UU No.11 year 2006. Him of Bureau status enableness of woman become Body, available [of] media supporter of enableness of woman in Aceh like P2Tp2, UPT. Expected with area autonomy of non equity and non equality of gender can overcome in Aceh. Enableness of Woman In Management of Regional Autonomy